Presenting a Model for Enhancing Coaching of School Principals - Shirkhan , Majid; Moazzami, Mojtaba; Ahmadi, Gholamali (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: The objective of this study is to propose a model for enhancing the coaching of school principals in Tehran. The research aims to identify the indicators, components, and dimensions relevant to coaching school principals, as well as to determine the influential factors and validate the proposed model. Methodology: This research employs a qualitative and exploratory approach, utilizing the meta-synthesis technique. The study involves a systematic review of 33 sources, which are then filtered down to 11 highly relevant sources. Additionally, interviews with 23 experts in the field of coaching are conducted to complement the data. The findings are categorized and analyzed to identify key themes and dimensions. Findings: The study identifies 56 indicators categorized into 14 components within 2 main dimensions: personal characteristics and organizational characteristics. Personal characteristics include traits such as communication power, patience, crisis management, and intelligence. Organizational characteristics cover aspects like creating an organizational chart for coaching roles, structural changes, and attention to the coaching process. Influential factors include personal limitations, informational barriers, coaching culture, conditions of students and principals, principal training, environment, and budget constraints. Conclusion: The proposed model for enhancing the coaching of school principals in Tehran emphasizes the importance of both personal and organizational characteristics. Effective coaching requires principals to possess strong communication skills, patience, and crisis management abilities, while organizational support involves structural changes and fostering a coaching culture. Addressing personal limitations, improving informational resources, and providing adequate training and budget are crucial for the successful implementation of the coaching model. The findings underscore the need for a holistic approach that integrates individual competencies with organizational strategies to enhance the professional development of school principals.